Mobilidade e vulnerabilidade socioambiental: um estudo de caso para Governador Valadares - Marina Cavaliéri Gomes (2019)
The decision to migrate is not always the only result of a purely weighted and individual choice, in which the costs and benefits of the movement are weighed. Migration often also reflects the socio-economic, political, and environmental contexts in which it is embedded. Exposure to environmental risks and the availability and reliability of ecosystem services affect migration directly and indirectly, since these services affect other drivers of migrations, such as the economic context. Thus, it is important to consider the context and characteristics of households in the study of migration and, more broadly, mobility. From this perspective, mobility or immobility responses to environmental issues are likely to be associated with socio-environmental characteristics and vulnerability of families and the context, and these responses may be a mechanism of adaptation (to environmental events) and reduction or aggravation of vulnerability. In addition, the speed and severity of environmental events may impose the adoption of mobility on individuals, as in the case of a rapid onset event. This dissertation consists of a case study about the association between socioenvironmental vulnerability and the strategies of (im)mobility adopted by individuals residing in the urban households of Governador Valadares. A conceptual framework was proposed as a synthesis of the literature discussion, in which vulnerability and mobility interact through two mechanisms (selectivity and adaptation), that could yield a gap of socio-environmental vulnerability of households according to their potential to migrate and migratory history. The main objective of this dissertation is to investigate if the mobility experiences lived up by the households in Governador Valadares are related to different levels and dimensions of socio-environmental vulnerability. For this purpose, a socio-environmental vulnerability index and mobility typologies were constructed using data from a probabilistic, mutli-stage sample of 1226 urban households collected between 2013 and 2016. The data are part of the project research Migração, Vulnerabilidade e Mudanças Ambientais no Vale do Rio Doce. The vulnerability index was developed using the Alkire-Foster (AF) method, which synthesizes information from the selected indicators into a single variable that represents the level and intensity of the vulnerability experienced by the household. Since part of the original indicators had different measurement scales and the theoretical dimensions of vulnerability required a probabilistic interpretation, a standardization of these variables was applied and the probability of its occurrence was calculated from the half-defined integral under the normal curve up to its standardized value. The application of the AF method also allowed the decomposition of socio-environmental vulnerability by subgroups of home mobility and vulnerability dimensions. This way, it was possible to qualify the households of each subgroup of mobility as vulnerable and to measure the intensity of this vulnerability from three major dimensions: exposure to risk, sensitivity, and adaptive capacity and resilience. The results suggest that although vulnerable households in the international mobility subgroup are more exposed to socio-environmental risks than those in the subgroup that have never experienced international migration, they are more resilient, better able to adapt to the occurrence of socioenvironmental problems and there are indications that they are less vulnerable than the other subgroup. Our findings also suggest that there is selectivity in international emigration, with the least vulnerable households sending emigrants abroad as a likely strategy to adapt to exposure to social and environmental risks. We also found the conditions at the household surroundings among the vulnerable would be the main aggravating factors of socioenvironmental vulnerability, and therefore should be priorities in any mitigating strategy aimed to curb vulnerability at the household level.